Implementasi Nilai-nilai Pancasila Melalui Tradisi Bersih Desa Kampung Keboan Kelurahan Mandan Kabupaten Sukoharjo - Susilo Wijayanto, Danar; Hanif Ibrahim, Fauzan; Al Azhar, Kahfi; Handayani, Feby Dwi; Tri Kresnajaya, Defaja; Yufriana, Aisyah; Ika Wardhani, Anisa; Nadhirotu Dhihniyya, Khusna; Benazir Kartika, Ringgit; Surya Damayanti, Indira (Society : Jurnal Pengabdian Masyarakat, 2023)
This community service research focuses on village clean-up activities held by the Keboan Village Community, Mandan Village, Sukoharjo District. Village cleaning activities are intended as a form of gratitude to God, asking for protection for the entire village community, and as a form of respect for the ancestors. This activity contains the practice of Pancasila values which are implemented in each series of event activities. This research was conducted using descriptive qualitative methods through case studies. Data collection was carried out through literature study, interviews, observation and documentation. The results obtained are that the people of Keboan Village, Mandan Village are still strong in maintaining and preserving the village's clean traditions. In its implementation, it includes the implementation of Pancasila values, including divinity, tolerance, unity through deliberation and social justice. This activity shows that Javanese traditions are still strongly maintained and preserved by the people of Kampung Keboan by implementing the values of Pancasila.